"I'm not in the truth business": the politics of climate change with pre-service teachers. Issue 2 (4th June 2018) - Damico, James S.; Panos, Alexandra; Baildon, Mark
Abstract : Purpose: This study was designed to be an agonistic encounter between two pre-service teachers from different academic disciplines and with opposing climate change beliefs. The purpose of this study was to create an opportunity for this pair of future educators to voice, acknowledge and engage their differences, rather than avoid or skirt them. Design/methodology/approach: Using a paired interview approach, two pre-service teachers discussed online sources about climate change. The analysis focuses on critical literacy practices of textual critique and reader reflexivity, considering how students from different beliefs and perspectives engage in agonism and negotiated practices. Findings: While there was evidence of the two students engaged in critical literacy practices of textual critique, most of this engagement with the sources remained more at a surface level with somewhat superficial criteria to evaluate the sources. The two students engaged reflexively during the interview discussion in terms of their academic disciplines and climate change beliefs. This reflexive work produced the most compelling exchanges during the interview discussion and pointed to two rich sites for agonistic engagement: their differing conceptions of reliability and their competing perspectives about the intersection of science and politics. Originality/value: Agonism offers a lens that helps ensure we understand that all pursuits toward facts and truth are necessarily contested as we engage with respected adversaries, not enemies we need to vanquish. There is an urgent need for dialogue across difference, especially for people in the increasingly polarized USA with complex topics and challenges such as climate change.